Students' Perceptions on The Use of Artificial Intelligence (AI) as English Learning Tools at SMK Model Patriot IV Ciawigebang - Sri Rahayu Pebriani; Yayan Suryana Suryana; Yuniarti (Darussalam English Journal (DEJ), 2025)
This study investigates students’ perceptions of Artificial Intelligence (AI) as a tool in English language learning at SMK Model Patriot IV Ciawigebang. With AI tools like ChatGPT, Grammarly, and ELSA increasingly used in education, understanding how students respond to these technologies is essential, particularly in vocational school contexts. The study employed a quantitative survey method involving 134 11th-grade students selected purposively based on their AI usage in English learning. Data were collected through a 16-item Likert-scale questionnaire and analyzed using descriptive statistics. The results show that 71.6% of students frequently used AI, and 74.7% believed AI could help improve their English proficiency. Most students expressed positive attitudes, 45.5% felt happy using AI, and 49.3% agreed it benefited their learning. Additionally, 54.5% found AI explanations helpful for understanding material. However, only 39.5% fully trusted AI’s writing corrections, and 42.5% were neutral or unsure, reflecting a cautious attitude toward its accuracy. Overall, students hold favorable but critical perceptions of AI. While they appreciate its role in enhancing comprehension and engagement, their trust in AI output remains measured. The findings suggest that AI integration in English learning should be supported with proper guidance and critical digital literacy. Keywords: Artificial Intelligence; English learning; students’ perception; vocational high school